On the findings of dinosaurs in the Crimea - A. V. Lopatin; A. О. Averianov (Известия высших учебных заведений: Геология и разведка, 2019)
Ornithopod dinosaur Riabininohadros weberae from the Upper Cretaceous (upper Maastrichtian) of the Crimean Peninsula (Besh-Kosh) shows a set of primitive characters of hind limbs observed in iguanodontids and basal ornithischians and is referred to as Styracosterna indet. The second dinosaur specimen from Crimea (Aleshino) is a fragmentary skeleton, including cervical and dorsal vertebrae. It possibly belongs to advanced iguanodontids or primitive hadrosauroids. Thus, in the Maastrichtian of the Crimean Peninsula, at least two dinosaur species coexisted.